Antioxidant and antitumor activity of trolox, trolox succinate, and α-tocopheryl succinate conjugates with nitroxides - Zakharova, Ol’ga D.; Frolova, Tat’yana S.; Yushkova, Yuliya V.; Chernyak, Elena I.; Pokrovsky, Andrei G.; Pokrovsky, Mikhail A.; Morozov, Sergei V.; Sinitsina, Ol’ga I.; Grigor’ev, Igor A.; Nevinsky, Georgy A. (European journal of medicinal chemistry, 2016)
A possible ability of twelve new derivatives of known antioxidants trolox (TroH), trolox succinate (TroS), α-tocopheryl succinate (α-TOS) containing nitroxyl radicals (1–12) to protect bacterial cells from spontaneous and peroxide-induced mutagenesis and their cytotoxicity against six different tumor cells as well as two normal cells were investigated and compared with that for TroH, TroS, α-TOH, and α-TOS for the first time. In contrast to TroH and TroS, all nitroxide derivatives 1–12 demonstrated not only antioxidant properties, but also suppress the growth of human tumor cells: myeloma, mammary adenocarcinoma, hepatocarcinoma, T cells leukemia, histiocytic lymphoma, and T-cellular leucosis. The IC50 values (24 - ≥ 300 μM) depend significantly on the compounds and type of tumor cells. Some compounds were capable to inhibit the growth of normal mouse (LMTK) and hamster (AG17) fibroblast cells and demonstrate very different ratios in inhibition of various tumor and normal cell lines. Some nitroxide conjugates showed pronounced selectivity in suppressing the growth of several cancer cells. Overall, several compounds may be promising in parallel as antioxidants and as specific inhibitors of some tumor cells growth. Among considered spin labeled conjugates the most perspective derivatives as antioxidants and as antitumor agents are the compounds containing pyrrolidine nitroxides. In contrast to spin labeled TroH, TroS and α-TOS conjugates 1–12 succinyl derivatives 13–15 were inactive in inhibiting the growth of any tumor cells. It means that for suppressing the cancer cells the compounds should contain in their structures fragments of TroH, TroS or α-TOS. [Display omitted] •Twelve new derivatives of trolox, trolox succinate, and α-tocopheryl succinate containing nitroxyl radicals were analyzed.•A cytotoxicity was tested in human tumor cells: myeloma, adenocarcinoma, hepatocarcinoma, T cells leukemia, histiocytic, lymphoma, and T-cellular leucosis.•Several trolox and α-tocopherylsuccinate nitroxides may be promising in parallel as antioxidants and as specific inhibitors of some tumor cells growth.•For suppressing of the growth tumor and normal cells the compounds should have in the molecules fragments of TroH, TroS or α-TOS.